Randomized Clinical Comparison of the Dual-Therapy CD34 Antibody-Covered Sirolimus-Eluting Combo Stent With the Sirolimus-Eluting Orsiro Stent in Patients Treated With Percutaneous Coronary Intervention: The SORT OUT X Trial. Issue 22 (7th April 2021) - Jakobsen, Lars; Christiansen, Evald H.; Freeman, Phillip; Kahlert, Johnny; Veien, Karsten; Maeng, Michael; Raungaard, Bent; Ellert, Julia; Villadsen, Anton B.; Kristensen, Steen D.; Ahlehoff, Ole; Christensen, Martin K.; et al.
Abstract : Background: Target lesion failure remains an issue with contemporary drug-eluting stents. Thus, the dual-therapy sirolimus-eluting and CD34+ antibody–coated Combo stent (DTS) was designed to further improve early healing. This study aimed to investigate whether the DTS is noninferior to the sirolimus-eluting Orsiro stent (SES) in an all-comers patient population. Methods: The SORT OUT X (Combo Stent Versus Orsiro Stent) trial, was a large-scale, randomized, multicenter, single-blind, 2-arm, noninferiority trial with registry-based follow-up. The primary end point target lesion failure was a composite of cardiac death, myocardial infarction, or target lesion revascularization within 12 months, analyzed using intention-to-treat. The trial was powered for assessing target lesion failure noninferiority of the DTS compared with the SES with a predetermined noninferiority margin of 0.021. Results: A total of 3146 patients were randomized to treatment with the DTS (1578 patients; 2008 lesions) or SES (1568 patients; 1982 lesions). At 12 months, intention-to-treat analysis showed that 100 patients (6.3%) assigned the DTS and 58 patients (3.7%) assigned the SES met the primary end point (absolute risk difference, 2.6% [upper limit of 1-sided 95% CI, 4.1%]; P (noninferiority)=0.76). The SES was superior to the DTS (incidence rate ratios for target lesion failure, 1.74 [95% CI, 1.26–2.41]; P =0.00086). The difference was explained mainly by a higher incidence of target lesion revascularization in the DTS group compared with the SES group (53 [3.4%] vs. 24 [1.5%]; incidence rate ratio, 2.22 [95% CI, 1.37–3.61]; P =0.0012). Conclusions: The DTS did not confirm noninferiority to the SES for target lesion failure at 12 months in an all-comer population. The SES was superior to the DTS mainly because the DTS was associated with an increased risk of target lesion revascularization. However, rates of death, cardiac death, and myocardial infarction at 12 months did not differ significantly between the 2 stent groups. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03216733.